Oral pain associated with cancer therapy, a pain medicine perspective. (8th November 2018) - Roldan, Carlos J; Chai, Thomas; Erian, Jennifer; Welker, John
Cancer therapy-induced oral mucositis (CTIOM) can cause intolerable oral pain resulting in difficulty in chewing, swallowing and speaking. Thus, leading to patients requiring aggressive measures, such as parenteral feeding, the placement of gastric feeding tubes and discontinuation of oncologic treatments. Although, pain is the debilitating symptom, current efforts seem to focus independently in the histological damage, not in pain and symptom care. Current strategies for managing pain from CTIOM entail maintaining oral hygiene and the use of oral rinses, topical anesthetics, prophylactic antimicrobials and systemic analgesics such as opioids. Novel therapies, such as methylene blue oral rinse, are being investigated, with positive outcomes. Therefore, there is a need to identify treatment modalities for pain of CTIOM. Ideally, this should be noninvasive, safe and cost-effective, while providing sustained analgesia.